Deep change : cases and commentary on reform in high stakes states - Ponder, Gerald; Strahan, David B.; Lieberman, Ann; Fullan, Michael (Research in curriculum and instruction., 2005)
This book presents cases of schools (Part One) and programs at the district level and beyond (Part Two) in which reform, while driven by high-stakes accountability, became larger and deeper through data-driven dialogue, culture change, organizational learning, and other elements of high performing cultures. Commentaries on cross-case patterns by Ann Lieberman and Michael Fullan and a chapter on "now what?" first steps provide implications for initiating deep change that results in improved student learning outcomes even in challenging activity settings.